2015
DOI: 10.1007/s10903-015-0168-2
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Amongst Filipino Migrants: A Review of the Literature and Ten-Year Institutional Analysis

Abstract: As one migrates from an area of low to high incidence of breast cancer their personal risk of developing breast cancer increases. This is however not equally distributed across all races and ethnicities. This paper specifically examines Filipino migrants. A literature review was conducted to summarize breast cancer incidence, screening practices and trends in treatment amongst Filipino migrants. In addition, a retrospective cohort study was conducted specifically examining the age in which Filipino women were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…Similar to a study by Simpson et al on the incidence of breast cancer among Filipino women in Canada, (28) our finding may have a profound effect on future screening mammography guidelines and the ideal age to start screening for breast cancer for women of Malay descent. According to current clinical practice guidelines in Singapore, all women aged 50-69 years are encouraged to attend yearly breast cancer screening.…”
Section: Discussionsupporting
confidence: 89%
“…Similar to a study by Simpson et al on the incidence of breast cancer among Filipino women in Canada, (28) our finding may have a profound effect on future screening mammography guidelines and the ideal age to start screening for breast cancer for women of Malay descent. According to current clinical practice guidelines in Singapore, all women aged 50-69 years are encouraged to attend yearly breast cancer screening.…”
Section: Discussionsupporting
confidence: 89%
“…Other studies have found East Asian women to be more likely to be diagnosed at an earlier stage than other ethnocultural groups [14, 42, 43] and to have tumours that are less likely to have spread at the time of diagnosis [43, 44]. More research is needed to explore the causes for these findings, but it is important to note that variation also exists within immigrant groups; for example, Filipino women may be at increased risk of more aggressive breast cancers when compared to other East Asian women [45]. Of note, although we did not find a difference in diagnosis of stage I-II vs. III-IV for immigrant women overall, Iqbal et al found that immigrant women overall in Ontario were significantly less likely than Canadian-born women to be diagnosed with stage I (vs. II-IV) breast cancer [43].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings also suggested that a significant proportion of this group had no apparent PCP visits in the look‐back period (15.2% overall and 21.0% of recent immigrants) and low proficiency in Canadian languages. As noted in a recent review article,25 there have been limited Canadian data reporting on breast screening rates for Filipino women who are BC's second largest population of screening‐age immigrant women. Thus, our study contributes important data on this population including a description of both screening patterns and characteristics of the screening‐age Filipino immigrant population in BC.…”
Section: Discussionmentioning
confidence: 99%